2011
DOI: 10.2214/ajr.10.5202
|View full text |Cite
|
Sign up to set email alerts
|

Distant Infusion of Saline May Enlarge Coagulation Volume During Radiofrequency Ablation of Liver Tissue Using Cool-tip Electrodes Without Impairing Predictability

Abstract: Va s c u l a r a n d I nt e r ve nt io n a l R a d io l og y • O r ig i n a l R e s e a rc h WEB This is a Web exclusive article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…when the area close to the electrode reaches a temperature around 100ºC. This conclusion could provide an explanation for the previous experimental results obtained with a hybrid applicator based on a cool-tip electrode combined with a low-rate interstitial infusion of hypertonic saline at 2 mm from the electrode surface and exactly in the middle zone [6]. To be more precise, the saline infusion at that point could significantly delay roll-off, which could be due to the saline impeding severe tissue desiccation at this point.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…when the area close to the electrode reaches a temperature around 100ºC. This conclusion could provide an explanation for the previous experimental results obtained with a hybrid applicator based on a cool-tip electrode combined with a low-rate interstitial infusion of hypertonic saline at 2 mm from the electrode surface and exactly in the middle zone [6]. To be more precise, the saline infusion at that point could significantly delay roll-off, which could be due to the saline impeding severe tissue desiccation at this point.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that the addition of hypertonic saline perfusion at 2 mm from the electrode surface improves the performance of the cooled electrode by increasing the volume of the coagulation zone obtained from the cooled electrode only [6,7]. This improvement is also associated with a delay in the emergence of roll-off [8].…”
Section: Radiofrequency (Rf) Ablation (Rfa) Is a Minimally Invasive Amentioning
confidence: 98%
“…The results suggested that the hybrid applicator could increase coagulation zone volume without reducing predictability [8]. The current study is a complementary assessment of that study.…”
Section: Introductionmentioning
confidence: 61%
“…The experimental setup has been previously described in [8]. Briefly, all the RF ablations were conducted with a CC-1 generator (Radionics, Burlington, MA, USA).…”
Section: Experimental Studymentioning
confidence: 99%
“…With current electrodes, large ablation zones can be obtained but their predictability and completeness is problematic. Size and shape of the ablation zone are highly variable and difficult to predict [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] even in the most standardised ex vivo experiments (Table 1). A standard deviation of the ablation diameter, especially the transverse diameter, of 0.5-1 cm is very common (Table 1).…”
Section: Introductionmentioning
confidence: 99%